Construction of the Qurâ€™anic Values as the Basis for Islamic Education Development: A Study of Abdullah Saeedâ€™s Thought - Moh. Muslih (Edukasia Islamika, 2020)
The present study aims to elucidate the construction of the values of the Qurâ€™an â€‹â€‹as the basis for the Islamic education development based on Abdullah Saeedâ€™s thought. The concept of a hierarchy of values initiated by Abdullah Saeed is a continuation of Rahmanâ€™s general principles, proposing a new way of looking at the ethico-legal verses in the Qurâ€™an, so that this concept is very pivotal in contemporary Qurâ€™anic studies. Framed in a library research with a content analysis, this study constructed a basic framework from the values â€‹â€‹of the Qurâ€™an. Abdullah Saeedâ€™s book entitled â€œInterpreting the Qurâ€™an: Towards a Contemporary Approachâ€ became the primary source in obtaining the data. Study findings reveal that the construction of the Qurâ€™anic values comprises obligatory, fundamental, protective, implementation, and instructional values. The construction â€‹â€‹can be adopted as the basis for Islamic education development regarding the institution, courses, values â€‹â€‹and culture. This study also demonstrates that Qurâ€™anic values-based Islamic education is completely projected to produce qualified and competitive human resources in the globalized age.